1997
DOI: 10.3168/jds.s0022-0302(97)76307-0
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Soaps of Olive Fatty Acids in the Diets of Manchega Dairy Ewes: Effects on Digestibility and Production

Abstract: Two experiments were carried out with dairy ewes to determine the effects of supplementation of calcium soaps of olive fatty acids at 10% of the basal diet on digestibility, roughage intake, milk production and composition, and response to early induced ovulation. The addition of calcium soaps of olive fatty acids to the diets of dairy ewes significantly decreased the digestibility of dietary dry matter but not the digestibility of other components. The digestibility of crude fat was enhanced. Voluntary intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…Huang et al (2008), when supplementing diets with 5% soy oil; Bell et al (2006), when supplementing diets with 6% safflower oil, in dairy cattle; and Casals et al (2006), when supplementing diets with 2.7% linseed, in dairy ewes, also failed to observe treatment effects on milk protein content. In contrast, other authors reported that milk protein decreases with fat supplementation (Wu et al, 1993, in cows;Pérez Alba et al, 1997;Casals et al, 1999, in ewes). The higher fat and protein daily yields (g/day) observed in the milk of HPO diet animals was a result of the greater milk yield registered in this group (Table 4).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Huang et al (2008), when supplementing diets with 5% soy oil; Bell et al (2006), when supplementing diets with 6% safflower oil, in dairy cattle; and Casals et al (2006), when supplementing diets with 2.7% linseed, in dairy ewes, also failed to observe treatment effects on milk protein content. In contrast, other authors reported that milk protein decreases with fat supplementation (Wu et al, 1993, in cows;Pérez Alba et al, 1997;Casals et al, 1999, in ewes). The higher fat and protein daily yields (g/day) observed in the milk of HPO diet animals was a result of the greater milk yield registered in this group (Table 4).…”
Section: Discussionmentioning
confidence: 49%
“…Our results concur with those of Wu et al (1993) and Bu et al (2007) in cows. Other studies, using saturated or protected fats (Grummer, 1991;Palmquist and Beaulieu, 1993, in cows;Pérez Alba et al, 1997;Gargouri et al, 2006, in sheep), report an increase in the percentage of milk fat. Results of dietary supplementation with unprotected oils rich in PUFA are quite varied.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported by Jenkins (2000) in steers fed with rapeseed oil rich in oleic acid, in which an increase in the t 11-18:1 content from 1.72% to 4.22% was observed. Likewise, Pérez Alba et al (1997) and Gallardo et al (2014) reported a drastic increase in the content of trans-18:1 and t 11-18:1 isomers, respectively, in dairy sheep that were also offered calcium soap of olive oil. However, Hristov et al (2005), in a study comparing sunflower oil rich in linoleic acid (76.5% linoleic acid) and sunflower oil rich in oleic acid (76.5% oleic acid) in concentrate lot steers, found no differences in the content of t 11-18:1 or c 9,t 11-18:2.…”
Section: Meat Qualitymentioning
confidence: 92%
“…These isomers could be transferred to milk fat or meat fat. A small number of studies carried out with olive oil in dairy sheep (Pérez Alba et al, 1997;Gómez-Cortés et al, 2008;Gallardo et al, 2014), feedlot lambs ) and suckling lambs (Manso et al, 2011;Gallardo et al, 2014) have reported an increase in oleic acid, a substantial increase in a wide variety of trans-monoene isomers and an increase in c9,t11-18:2 in milk and meat. Spain is the world's most important producer of olive oil, and when it is refined for human consumption a large quantity of by-products are formed, which are often used in animal feeds.…”
Section: Introductionmentioning
confidence: 99%
“…Oleic acid is the major monounsaturated fatty acid (MUFA) in ruminant feeds, and some studies have reported increases in this FA in milk and lamb meat when olive oil (OLI) is added to the diet (Pérez Alba et al, 1996;Manso et al, 2011). Adding marine oils to dairy ewe diets has also proven to be an effective nutritional strategy for enhancing the milk content of some bioactive FAs, such as cis-9, trans-11 18:2 (RA), its precursor trans-11 18:1 (VA) and, to a lesser extent, n-3 FAs (Toral et al, 2010a and2010b).…”
Section: Introductionmentioning
confidence: 99%